MANAJEMEN KURIKULUM PESANTREN DI ERA GLOBALISASI (STUDI KASUS DI PONDOK PESANTREN HIDAYATUL MUBTADIIN) - Muhammad Rizki Romadhon (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This research was conducted using a qualitative approach with a phenomenological case study design. The setting of this research was at Hidayatul Mubtadiin Islamic Boarding School with research subjects at Hidayatul Mubtadiin Islamic Boarding School. As for the techniques in collecting data in this study using three methods, namely observation (observation), interview (interview) and documentation (documentation). Developed into a boarding school that manages two types of educational curricula, namely the pesantren education curriculum and the formal education curriculum. The curriculum is integral, which means that the activities carried out support each other and are still in one series. Second, the management developed at the Hidayatul Mubtadiin Islamic boarding school is as follows: 1) planning which includes the vision, mission, goals, functions and values ​​that must be carried out by the students; 2) organizing which includes Islamic boarding schools curriculum, formal education curriculum and skills education based on IT and foreign languages; 3) the application is carried out using Islamic boarding school teaching methods and educational methods applied by the government; and 4) control is carried out to measure the ability of students to master the knowledge that has been studied. Third, the existence of the Islamic boarding school curriculum in the global era can be seen from two types of relevance, namely academic relevance and social relevance. Academic relevance can be seen from the existence of formal educational institutions, leadership training, organization, and providing foreign language and information technology skills.